IDDF2022-ABS-0129 AN OVERVIEW OF MICROSCOPIC COLITIS IN ABERDEEN. (2nd September 2022) - Taj-Aldeen, Wamedh; Clark, Clare; Siu, Wilson; Galloway, Mary; Smith, Malcolm
Abstract : Background: Microscopic colitis (MC) is one of the recognised causes of chronic diarrhoea. It is an inflammatory disease of the colon that is characterised by watery, non-bloody diarrhoea. It often presents in middle-aged groups and affects women more than men. The colon usually appears normal macroscopically and tissue biopsy reveals either lymphocytic or collagenous collitis. In this retrospective observational study, we assessed the epidemiology, risk factors and treatment response in a single large centre. Methods: Data were collected between January 2008 and December 2017. The source of information was the Pathology lab in Aberdeen Royal Infirmary and the track care system. The initial sample had 139 patients; 39 patients were excluded later on due to either no follow-up or due to non-specific histological changes after discussing them in the departmental pathology meeting. Basic demographics, aetiology, symptoms and response to treatments were all recorded. Results: The record of 100 patients were reviewed, 77 women and 23 men. The average age was 61 (IDDF2022-ABS-0129 Figure 1), and although the exact aetiology was not obvious in 65 patients, 25 patients were found to have recognised risk factors (medications, rheumatological disease, coeliac or infection). Interestingly, 15 patients with histological diagnosis of MC (collagenous and lymphocytic) had also malignancy which points to some relationship between both conditions (IDDF2022-ABS-0129 Figure 2). Although there is no indication for faecal calprotectin level, 11 patients had this test done with 7 negative results and 4 marginally raised levels. With regard to the treatment, 15 patients had a spontaneous recovery, 36 responded to budesonide, while 18 responded to mesalazine. On the other hand, 9 patients didn't respond to conventional treatment, 6 of them required prednisolone and 3 patients started on an immune modulator (azathioprine). 95 patients had watery diarrhoea as the main symptoms, 3 patients with altered bowel habits, while 2 complained of constipation. Conclusions: A considerable number of patients recover spontaneously (self-limited) or require anti diarrheal agents like loperamide only. Although biological treatment has not been used yet in patients with microscopic colitis in Aberdeen, there is good evidence that anti-TNF agents can induce remission in patients with refractory disease.